Unilateral syndactyly, hemihypertrophy, and hyperpigmentation with mosaic 2q35 deletion - Akhtar Ali; Ajeet Kumar; Pawan K Dubey; Vivek Pandey; Ankur Singh (Wolters Kluwer Medknow Publications, 2023)
Pigmentary mosaicism (PM) is a clinical condition of dyspigmentation with chromosomal abnormality. PM presents with both cutaneous and extracutaneous manifestation. Hypomelanosis of Ito and linear and whorled nevoid hypermelanosis are syndromic disorders in which PM is one of the manifestations. We present a case of a 1-year-old child with a unique constellation of symptoms of unilateral syndactyly, hemihypertrophy, and skin hyperpigmentation. Karyotype from peripheral blood was normal. We found genetic aberration (mosaic 2q35 deletion) in the present case from fibroblast cultured from the affected area. This unique constellation of symptoms was previously reported once but genetic study was not done from the affected tissue. This case highlights the need of considering fibroblast culture-based genetic study rather than doing simple karyotype from peripheral blood. Genetic study also established the molecular basis of symptoms in the above case.